The Main Point of the Professional Context of the Future Primary School Teacher - Zhelanova, Viktoriia (Pedagogical Discourse, 2015)
In the article the phenomenon of the professional context of the future primary school teacher and its semantic constituent – the notion «context» and its sphere of realization – contextual teaching of the future primary school teacher are examined. The attention is paid to the inter-discipline sources and integral nature of the notion «context». It is found out that the linguistic, philosophical and psychological interpretation of the context is accumulated in its pedagogical interpretation which is connected with the phenomenon of professional context. It is proved that professional context is the unity of inner and outer context where the inner context is treated by the author as a professional personal context that reflects the qualities which are typical for the primary school teacher as a representative of a certain profession. These are motivation, reflexive competence, sense and professional subjectivity. The outer context is interpreted as a social context connected with socio-cultural, space-time, pracsiological, communicative characteristics of professional activity. Hence the inner professional context embraces motivational-stimulating, reflexive-formative, sense creating and subjective-formative types of context; the outer context includes communicative formative type.